Social Capital and Female Entrepreneur, Challenges and Opportunities: A Study of Multan - Mahmood, Shahzad; Riaz, Hira (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this paper is to examine the challenges female entrepreneurs face in the development of their business in the context of Multan. In so doing, it addresses a gap in the literature on the experiences of female entrepreneurs in a Southern Punjab context and acknowledges the contribution that women make in this area of work. The paper draws on survey data from 100 female entrepreneurs currently engaged in their businesses in district Multan– a Southern Punjab District in Pakistan. Results indicate that female entrepreneurs are generally confident and resourceful and that they enjoy the challenge of entrepreneurial activity. As in the other areas, they experience difficulties relating to family commitments and access to finance – as well as problems gaining acceptance and accessing networks.